(3CKQ hSGFd GdJhGUd GdGLJeGYj Ydi UMI GdCSQI aj GdQHGW HGdeZQH (B:s ((3OQGSI aj GdGfKQhHhdhLj```G GdGLJeGYjI(B) / s - (3aLQ SejQ GdMQjU,s; (3SYO YHO GdefYe HQcgs; (3Sdhi jhSa OQhjTs; (3JGeQ LGO QGTOs (2023)
(3gOaJ GdOQGSI GdMGdjI Edi GdJYQa Ydi JCKjQ GSJNOGe hSGFd GdJhGUd GdGLJeGYj hNGUI ajS Hhc Ydi UMI GdehGWfjf HeOjfI GdQHGW HGdeedcI GdeZQHjI(B. (3hbO JHfJ GdOQGSI GdMGdjI cd ef fXQjI JcfhdhLjG hSGFd GdEYdGe hJCKjQgG Ydi GdeLJeYGJ, fXQjI GdESJNOGeGJ hGdETHGYGJ, hfXQjI GdEYJeGO Ydi hSGFd GdEYdGe cEWGQ fXQj ddOQGSI(B. (3Pdc aVdG Yf GSJNOGe GdefgL GdCfKQhHhdhLj hGdeONd GdHjhKbGaj cCWQ efgLjI ddOQGSI(B. (3MjK GYJeOJ GdOQGSI Ydi GSJeGQI GdGSJHjGf aj UjZJgG GdGdcJQhfjI cCOGI dLeY HjGfGJ GdOQGSI ef CaQGO GdYjfI GdHMKjI, hbO JchfJ YjfI GdOQGSI ef (B(100) (3aQO ef ehGWfj eOjfI GdQHGW(B. (3hbO JhUdJ GdOQGSI Edi YOO ef GdfJGFL dYd ef CHQRgG, Cf hSGFd GdJhGUd GdGLJeGYj GSJWGYJ Cf JDKQ Ydi UMI eSJNOejgG HTcd eHGTQ cGdJCKjQ Ydi UMI GdYjf hGdEHUGQ hGdUOGY hZjQgG ef GdJCKjQGJ GdYVhjI, hCjVG HTcd ZjQ eHGTQ cEQJaGY eYOdGJ GdEUGHI HCeQGV bdI GdMQcI fJjLI GdLdhS hGSJNOGe Jdc GdhSGFd dSGYGJ WhjdI Ohf GdJMQc hCjVG GdJCKjQ Ydi eOi GdhYj GdUMj ddeSJNOejf SdHG hEjLGHG, hbO GeJO Pdc GdJCKjQ djTed cdG ef GdUMI GdGLJeGYjI, GdUMI GdfaSjI, hCjVG GdUMI GdHjhdhLjI Ch GdYVhjI(B.s
The current study aimed to identify the impact of the use of social media, especially Facebook, on the health of citizens in the city of Rabat, Kingdom of Morocco. The current study adopted each of the theory of media technology and its impact on societies, the theory of uses and gratifications, and the theory of dependence on the media as a theoretical framework for the study. This is in addition to the use of the anthropological approach and the bicultural approach as methodological frameworks for the study. The study relied on the electronic form of the questionnaire as a tool for collecting study data from the research sample, and the study sample consisted of (100) individuals from the city of Rabat. The study reached a number of results, perhaps the most prominent of which is that social media has been able to affect the users' health directly, such as affecting eye health, vision, headaches, and other organic effects, and also indirectly, such as high rates of immobility diseases as a result of sitting and using these means for hours without moving and also affecting the health awareness of users positively or negatively, this influence has extended to include social health, mental health, and also biological or organic health.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2023. s
(3HHdjhLQGajG(B: (3UaMGJ (B196-215.s
(3UOQ GjVG cbQU eOeLs
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3hSGFd GdGYdGes -- (3GdeZQHs; (3hSGFd GdJhGUd GdGLJeGYis; (3hSGFd GdJhGUd GdGLJeGYj s -- (3GdQHGW s -- (3ajS Hhcs -- (3GdUMIs -- (3GdeZQH s